Estate Agent - Waller T; South Africa; Nafte Debbie (South Africa: Awareness Publishing Group (Pty) Ltd, 2010)
An a introduction to the job of Estate agent, describing the work of an estate agent, the skills and personal qualities required, school subjects that are helpful, and the training and opportunities that are available. the book can help learners to decide if this is suitable careerfor them.
Junior Non-Fiction -; Juvenile literature